Training Balance Analysis Of 3 Kg LPG Tube Retester Repair Using Ranked Positional Weight Method In PT. Earth Trans Energy Wajo Regency South Sulawesi Province - Reza Rezaldy; Lamatinulu Ahmad; Muhammad Dahlan (Journal of Industrial System Engineering and Management, 2022)
PT. Bumi Trans Energi is one of the companies engaged in 3 Kg LPG cylinder retested repair, this company repairs 3 Kg LPG cylinders that have been damaged for 5 years, damage to the handguard, and footring, and welded joints on the tube. In the repair process, there are 5 stations and 21 work processes, PT. Bumi Trans Energi encountered a problem in the repair line at station 1, and a bottleneck occurred. This bottleneck occurs because the production flow is not smooth from one station to the next, this problem causes each work station in the repair path to have a different speed level, which causes material accumulation between work stations, and waiting times between work stations. For this reason, this study aims to determine the number of workstations needed to get maximum efficiency and balance the repair process line when bottlenecks occur. Observations were made in data collection 30 times, each work element was observed and calculated in the data uniformity test and data adequacy test to obtain standard time. The results of this study were the application of 3 work stations from 5 initial work stations, there was a reduction in idle time to 425,74 seconds ( 7 minutes) following the increase in track efficiency to 84,17 % the balance delay decreased to 15,83 %, and the Smoothness Index was 212,63. The actual idle time was 1004,97 seconds (17 minutes) while the proposed trajectory idle time used the Ranked Positional Weight method of 425,74 seconds (7 minutes). The difference between actual and proposed idle time is 10 minutes, and the placement of work elements at work station 1 (one) consists of 9 work operations, while work stations 2 (two) consist of 1 work process, and work stations 3 ( three ) consist of 8 work processes